(untitled) (Philosophy and Progress, 2022)
Jainism is a religio-philosophical school of India which reacted against the Brahmanic/Vedic tradition and established as a school of thought. As a way of life it started as a Sramanic movement (the non-Brahmanic ascetic tradition) to attain the truth. Jains metaphysics and epistemology are purely logical and conducive for all. Jainism always is against the physical and psychological violence, and believes that it is the Ekanta (one sided view of reality) philosophy, which leads to violence. According to the Jains, Ekantavada is a very rigid view, thus partial in nature. Any school asserting this claim for the absolute truth logically thus rejecting all the other views that basically leads towards dogmatism and in toleration; which further aggravated and leads toward violence. Mahavira as a champion of Ahimsa (nonviolence) carried out this concept from the domain of practical behaviour to the domain of intellectual and philosophical discussion. The Jaina principle of respect for the other life gave rise to the principle of respect for the views of others; thus they advocates Anekāntavāda. According to them, non-violence is the goal and Anekāntavāda becomes the tool. Its Syadvada is basically a logical inclusivity which accepts diversified aspects of truth. Consequently, it tells that a complete understanding of any truth requires the consideration and acceptance of a variety of viewpoints. This pluralistic view of the Jains is to be effective well to combat social violence and evils too. The world is in the pyramid of violence that can only entail massive destruction of this phenomenal world in any moment. I think, this pluralistic approach of Anekāntavāda is to be considered as the panacea to overcome all types of rigidities and bigotries of the present society as well. Philosophy and Progress, Vol#67-68; No#1-2; Jan-Dec 2020 P 15-31